Functions and Benefits of Arts Education in the Perspective of Ki Hajar Dewantara - Indah Wijayanti; Herman Nirwana; Dina Sukma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Ki Hajar Dewantara's concept of education can still be applied, but adjustments are needed to current developments. Education that is national in nature and nationalism is always needed to educate the independent spirit of the nation's children to be able to maintain unity and integrity and always love their homeland so that they are able to think and behave independently for the progress of the nation. The cultural approach taken by the teacher is the uniqueness of Ki Hajar Dewantara's concept of education in early childhood. In addition, the application of Ki Hajar Dewantara's educational concept related to the provision of learning activities that can develop children's senses in Taman Indria Ibu Pawiyatan Yogyakarta and Taman Indria Jakarta, is quite good. The arts, which are placed in the Tamansiswa 'Pancadharma' circle, are also used in education in Indonesia, because the arts used as an educational tool in Tamansiswa are intended to influence the development of children's souls towards beauty in particular, but beauty in its series with nobleness and subtlety, so that it is suitable for civilised and cultured human life. Art also needs to be based on national life in a broad sense, not against humanity and not against the law.